Learning Media Based on Computer Simulation for Effective Parabolic Motion Learning - Afrizal Mayub (CV Media Inti Teknologi, 2023)
This study aims to (1) produce a computer simulation-based parabolic motion learning program, (2) describe the effectiveness of computer simulation-based parabolic motion learning, (3) describe the level of effectiveness of parabolic motion learning using computer simulation. The research method consists of; First, software engineering research is to create a Parabolic motion simulation learning program based on computer simulation including: analysis, design, code, and testing. Second, research to see the effectiveness of computer simulation baseParabola motion simulation learning programs. Sampling using total sampling technique. Based on this, the researchers determined a sample of all Science Masters students in semesters 1 and 3 for the 2021/2022 academic year as many as 40 people. The results showed that computer simulation-based Parabolic motion simulation learning programs were effective in learning, this can be seen from the N-Gain value of 0.65 which is included in the high or very effective category. Based on a two-dimensional motion simulation questionnaire based on computer simulation, it is effectively used for two-dimensional motion material, this can be seen from the score obtained at 4.4 (on a scale of 1-5), namely in the effective category.